Structural Evaluation of Flexible Pavement with 2017 Road Pavement Design Manual (MDP) and 2017 Austroads Method (Case Study: Tanah Runtuh – Tawaeli National Road Section) - Ligar Fitrianingsih; Bambang Sugeng Subagio; Aine Kusumawati (Institut Teknologi Bandung, 2022)
Abstract National roads in urban and rural areas use flexible pavement in general. If damage occurs on the pavement, structural road maintenance can be analyzed. The most commonly used evaluation for structural pavements is conducting a deflection survey using the Falling Weight Deflectometer (FWD) tool, where the results from the deflection evaluation can be used to determine the overlay. This research aims to conduct a structural evaluation of the Tanah Runtuh – Tawaeli National Road section and determine the required overlay thickness using the 2017 MDP and Austroads method. The road segment is divided into STA 10+000 to 12+656 and STA 14+400 to 18+700. The required overlay thickness using the 2017 MDP for average pavement temperatures of 47°C, 42°C, 41°C, 38°C, and 35°C is 80 mm for both segments. The required overlay thickness using Austroads method is 114mm and 98mm for a temperature of 47°C, 105mm for a temperature of 42°C, 97mm for a temperature of 41°C, 85mm for a temperature of 38°C, and 83mm for a temperature of 35°C. The analysis results using the 2017 MDP is not affected by the pavement temperature, meanwhile the overlay thickness from the Austroads method show that the pavement temperature affects the required overlay thickness. Key words: Flexible pavement, deflection, FWD, overlay thickness, MDP 2017, austroads. Abstract Jalan nasional di perkotaan maupun luar kota masih umum menggunakan perkerasan lentur. Apabila terjadi kerusakan pada perkerasan dapat dilakukan pemelihaaran jalan secara struktural pada perkerasan tersebut. Evaluasi yang paling umum digunakan untuk struktural perkerasan adalah dengan melakukan survey lendutan dengan menggunakan alat Falling Weight Deflectometer (FWD) yang mana hasil dari evaluasi lendutan dapat digunakan untuk menentukan lapis tambah (overlay). Penelitian ini bertujuan untuk melakukan evaluasi struktural pada ruas jalan Nasional Tanah Runtuh – Tawaeli dan menentukan tebal lapis tambah menggunakan metoda Manual Desain Perkerasan Jalan 2017 dan Austroads. Ruas dibagi menjadi 2 (dua) segmen yaitu segmen STA 10+000 s/d 12+656 dan STA 14+400 s/d 18+700. Kebutuhan tebal lapis tambah menggunakan metoda MDP 2017 untuk nilai temperatur rata-rata perkerasan 47°C, 42°C, 41°C, 38°C, dan 35°C adalah 80 mm untuk kedua segmen. Kebutuhan tebal lapis tambah dengan menggunakan metoda Austroads adalah 114 mm dan 98 mm untuk temperatur 47°C, 105 mm untuk temperatur 42°C, 97 mm untuk temperatur 41°C, 85 mm untuk temperatur 38°C, dan 83 mm untuk temperatur 35°C. Hasil analisis dengan menggunakan metoda MDP 2017 tidak dipengaruhi oleh temperatur perkerasan, sementara tebal overlay yang dihasilkan dari metoda Austroads menunjukkan bahwa temperatur perkerasan mempengaruhi tebal overlay yang dibutuhkan. Key words: Flexible pavement, deflection, FWD, overlay thickness, MDP 2017, austroads.